The Phenomena of the Seven Textual Standards in Literary Texts (Utilization of Cohesion in “Kalila and Dimna”) - Muhammad Haziq Bin Ariffain; Solehah Binti Yaacob (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2024)
Since the text linguistics study was invented, its role as a tool of text analysis may not fully recognized. Besides, it mostly covered the study of contemporary text, though it was used by some scholars in analysing of Arabic classical texts. Yet, some scholars were refused to use it as it was seemed not suit on literary study field. Meanwhile, there were rhetorical study which can be focused on that field. Unfortunately, researcher was seeing this in a opposite side. Whereas there is a scholar named Robert de Beaugerande who invented and standardized the standard way of text analysing so called the Seven Standards of Textuality and develop them on English linguistic studies. Thus, by knowing their significance in linguistic studies, this study aims to approach one of the Seven Standards which is Cohesion and study it practically on the “Kalīla wa Dimna” as classical literary texts, seeking for the linguistic values of texts and prove the effectiveness of study. The result of this reserch is that the seven textual standards established by Robert de Beaugrand have many functions that are important during the study of written texts, especially while analyzing them within the framework of as-sabk, which is one of the most important criteria in text formation and interpretation.